The Perception Of Jordanian Political Parties Toward Iraqi Refugees And Political Stability In Jordan - Albrizat, Rayeq Saleem Eid (2013)
A massive number of Iraqi refugees fled to Jordan post the 2003 American invasion in a desperate attempt to preserve their lives. The relatively enormous number of refugees in comparison to Jordan‟s population negatively influenced the economic and political conditions in Jordan. Literature indicated that the influx of Iraqi refugees have contributed to increase in prices, unemployment and political insecurity through acts of terrorism. This study investigates the perception of Jordanian political parties toward Iraqi refugees and their impact on political stability through economic and political security factors. The perception theory is implemented to measure the parties‟ members perception based on their attitudes, knowledge and experience of the political stability impacted by Iraqi refugees. The perception has been investigated through combination of quantitative and qualitative methods, namely questionnaires, interviews and secondary data from related documents. The study sample consisted of 410 members of 16 political parties and their local branches in 5 governorates in Jordan. Eight parties‟ leaders were interviewed in person to assess their views about the refugees‟ situation.